Innovative Strategy of Management for Developing 21st Century Skills-Based Curriculum in Modern Schools - Ratnawati Susanto (Universitas Pendidikan Ganesha, 2026)
The increasing cultural diversity of students in international schools poses challenges for teachers in effectively managing student behavior, particularly due to differences in norms, values, and communication patterns. This condition demands the implementation of inclusive and culturally sensitive pedagogical strategies to create a harmonious learning environment. This study aims to analyze the relationship between cross-cultural communication competencies, student behavior management strategies, the implementation of inclusive learning, and the effectiveness of multicultural classroom management. This study uses a mixed methods approach involving teachers as research subjects. Data collection was conducted through Likert scale questionnaires and in-depth interviews. Data analysis used descriptive statistics, correlation tests, multiple linear regression, analysis of variance, and thematic analysis for qualitative data. The results of the study indicate a significant positive relationship between all variables, where inclusive learning is the most dominant factor in increasing the effectiveness of multicultural classroom management. Qualitative findings reveal that the implementation of a cross-cultural approach by teachers can improve discipline, empathy, and collaboration among students. The conclusion of this study confirms that inclusive pedagogy based on cultural sensitivity plays an important role in strengthening a harmonious classroom climate. The implications of this research indicate that cross-cultural communication training and inclusive learning strategies need to be prioritized in teacher professional development to improve the quality of multicultural classroom management.